Pengaruh Viral Marketing, Brand Ambassador dan Kemudahan Penggunaan terhadap Keputusan Generasi Z Menggunakan Aplikasi Allo Bank - Muslikhah Fitri Wilarto; Maruji Pakpahan; Yugi Setyarko (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effect of Viral Marketing, Brand Ambassador, and Perceived Ease of Use on Generation Z’ decision to use the Allo Bank application. This research employs a quantitative research design and uses a purposive sampling technique. The population in this study is unknown. A total of 105 respondents were selected as the sample using a non-probability sampling method and the Lemeshow formula. Data were collected by distributing questionnaires. The research instrument was a questionnaire measured using a Likert scale. The data were analyzed using SPSS version 26 and Microsoft Excel. The results indicate that, partially, Viral Marketing has a significant effect on the decision to use the application, Brand Ambassador has a significant effect on the decision to use the application, and Perceived Ease of Use has a significant effect on the decision to use the application.